L’accélération de l’intégration du commerce extérieur des pays de l’ASEAN au marché mondial - De Koninck, Rodolphe; Comtois, Claude (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1980)
For the period 1965-1977, for each of the five ASEAN member countries (Thailand, the Philippines, Malaysia, Indonesia, Singapore) as well as for the whole of the region, were examinee the evolution of the volume and of the components of the import and export trade, as well as that of the proportional share of the various trading partners. The following tendencies are apparent. 1) The region's national economies are increasingly « world trade oriented ». 2) Since the founding of ASEAN in 1967, the proportional share of intraregional trade has been declining. 3) The composition of this trade is increasingly determined by the needs of industrial countries. 4) The proportional share of the trading carried out with industrial countries, and particularly with Japan, is also increasing. 5) Singapore seems to play a key role in this articulation of the integration of the region to the world market, an integration detrimental to regional internal integration, an official goal of the ASEAN.